Molecular titanium–hydroxamate complexes as models for TiO2 surface binding. Issue 14 (19th January 2016) - Brennan, Bradley J.; Chen, Jeffrey; Rudshteyn, Benjamin; Chaudhuri, Subhajyoti; Mercado, Brandon Q.; Batista, Victor S.; Crabtree, Robert H.; Brudvig, Gary W.
Abstract : Molecular titanium(iv ) hydroxamate complexes were synthesized and used as models to determine the hydroxamate–metal oxide surface binding motif on TiO2 . Abstract : Hydroxamate binding modes and protonation states have yet to be conclusively determined. Molecular titanium(iv ) phenylhydroxamate complexes were synthesized as structural and spectroscopic models, and compared to functionalized TiO2 nanoparticles. In a combined experimental–theoretical study, we find that the predominant binding form is monodeprotonated, with evidence for the chelate mode.